Distance and protective barrier effects on the composite resin degree of conversion - Margareth Coutinho; Natália Carvalho Trevizam; Renata Nakase Takayassu; Ariene Arcas Leme; Giulliana Panfiglio Soares (Wolters Kluwer Medknow Publications, 2013)
Context: The food wrap films are used to cover the tip of curing light units in order to avoid contamination and prevent damage to the light guide. However, their effects on resin polymerization are not fully known. Aims: We investigated the effects on restoration efficiency of a food wrap protective barrier used on the tip of curing light units. Materials and Methods: For each treatment, five replications were performed, a total of 60 bovine incisor. The degree of conversion (%DC) of restorations with the composite resin Opallis EA2 was evaluated using 3 curing light devices (Optilux 501, Optilight and Ultra LED) and 2 curing distances (0 and 5 mm). The composite resin was tested for restoration of cavities in bovine crowns. %DC values were measured by the Fourier transform infrared spectroscopy-attenuated total reflectance technique. Statistical Analysis Used: The data were analyzed using 3-way ANOVA and Tukey's test. Results: Use of the protective film lowered %DC ( F = 4.13; P = 0.05), and the effects of curing distance were associated to the curing light device ( F = 3.61; P = 0.03). Conclusions: The distance from the light curing tip and use of a translucent protective barrier on the light-cure device can both impair composite resin %DC.